Reducing the intensity of thermal radiation at the sublayer extinguishing of alcohols by ecologically acceptable aerosols - Balanyuk, Volodymyr; Kravchenko, Anton; Harasymyuk, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2021)
This paper has theoretically substantiated and experimentally established the intensity of thermal radiation at burning and sublayer extinguishing of alcohols with environmentally acceptable aerosols. An installation has been improved that determines the effectiveness of sublayer extinguishing with fire-extinguishing aerosols; a procedure that has been devised for determining the intensity of thermal radiation implies equipping it with an additional heat flow meter HFM–01 at a distance of 30 and 60 mm. The task to establish the intensity of thermal radiation when burning alcohols and its impact on the process of sublayer extinguishing of alcohols with aerosols has been solved. The dependence of sublayer extinguishing efficiency on thermal radiation implies that the fire extinguishing aerosol completely shields the surface of the combustible liquid against its action. The result of this study has established that the intensity of thermal radiation at a distance of 60 and 30 mm from the surface of an alcohol flame with an area of 234 cm2 ranges from 0.8 to 4.7 kW/m2; the intensity of burning and, accordingly, radiation, maximizes on seconds 30‒40 of burning. It has been found that the intensity of thermal radiation for ethanol decreases with the addition of an aerosol with an intensity of up to 0.2 g/s, and decreases even more at the intensity of supply from 1.2 g/s. With a further increase in the intensity of aerosol supply, the radiation intensity begins to decrease, probably due to a decrease in the rate of combustion. In this case, the flame first decreases in size up to 2 times, and then, after 2‒3 seconds, it goes out. The use of fire-extinguishing aerosol for the sublayer extinguishing of alcohols ensures the effect of several factors that synergize and reduce the intensity of evaporation, burning, and, accordingly, thermal radiation